(untitled) (Bioscience Journal, 2019)
Research using anaerobic filters as alternative materials to gravel becomes fundamental, especially if they are low cost, accessible and have high efficiency in the treatment of swine wastewater. This study aimed to evaluate the efficiency of anaerobic filters with different types of support media, as an alternative to gravel, in the treatment of swine wastewater. We carried out the experiment in a completely randomized design. The treatments were composed of anaerobic filters with four different media (gravel, bamboo, luffa sponge and foam), three replications in a time-repeated measurements scheme (0, 60, 120, 180 and 240 days post-filter establishment). To determine the efficiency of removal by the filters, we performed analysis of turbidity, total solids, biochemical oxygen demand (bod), total n and total p in the affluent to and effluent from the filters. Among the alternative media, bamboo presented an efficiency of removal of the evaluated attributes similar and, in most cases, superior to gravel. From 60 to 180 days of filter operation, the luffa sponge remained with high turbidity and total solids removals, with the greatest decrease at 240 days of operation. After two months of filter operation, the alternative support media exhibited bod and total n removal similar to that of gravel. At 240 days of operation, the filters containing luffa sponge and bamboo showed the highest total p removal.